2019
DOI: 10.1088/1361-6455/ab2b58
|View full text |Cite
|
Sign up to set email alerts
|

The effects of trap-confinement and interatomic interactions on Josephson effects and macroscopic quantum self-trapping for a Bose–Einstein condensate

Abstract: We theoretically study the effects of trap-confinement and interatomic interactions on Josephson oscillations (JO) and macroscopic quantum self-trapping (MQST) for a Bose-Einstein condensate (BEC) confined in a trap which has a symmetric double-well (DW) potential along zaxis and 2D harmonic potentials along x-and y-axis. We consider three types of model interaction potentials: contact, long-range dipolar and finite-range potentials. Our results show that by changing the aspect ratio between the axial and radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…5(b). The self-trapping effect has been obtained previously in our group [65] for non-dipolar cold atoms trapped in a double well in case of strong confinement i.e. the asymmetry parameter λ << 1.…”
Section: Effect Of Coherent Coupling On the Dynamics Of Population In...supporting
confidence: 62%
See 1 more Smart Citation
“…5(b). The self-trapping effect has been obtained previously in our group [65] for non-dipolar cold atoms trapped in a double well in case of strong confinement i.e. the asymmetry parameter λ << 1.…”
Section: Effect Of Coherent Coupling On the Dynamics Of Population In...supporting
confidence: 62%
“…We considered three types of interaction potentials (i) contact, (ii)long range dipolar and (iii) finite range potentials. We found that by varying the aspect ratio of the trap (i) transition from JO to MQSt occurs for small atom-atom interactions (ii) transition from Rabi to JO and JO to MQST occurs for long range dipolar interaction and transition from JO to MQST occurs even if scattering length is relatively large in the region of narrow Feshbach resonance due to finite range effects [65].…”
Section: Introductionmentioning
confidence: 91%
“…The other three interaction parameters U i , K and I are usually smaller than U by two orders of magnitude for small r 0 , otherwise they show the similar dependence on | | a s as in the case of U. However, for the condition κr 0 =1, which may apply to a narrow Feshbach resonance, U may become zero or negative near the resonance while the the other three interaction parameters remaining finite [39]. There one might find the other interaction parameters (U i , K, I) comparable to the onsite interaction (U).…”
Section: Building Up the Models: Calculation Of Interaction Parametersmentioning
confidence: 85%
“…For small | | a s regime, U varies almost linearly with | | a s as in the case of contact interaction. In the other condition κr 0 =1 for positive a s , U varies highly nonlinearly as shown in [39]. So far we have presented the results on U only.…”
Section: Building Up the Models: Calculation Of Interaction Parametersmentioning
confidence: 87%
“…The former geometry is adapted for matter wave interferometry [33,34,37], while the latter enables the realization of atomic circuits [21,23,[38][39][40]. The effective dimension is crucial to determine the excitations involved in the dynamics [41,42]: in three dimensions vortex lines decaying into vortex rings [43], in two dimensions point-like vortices carrying phase-slips [44,45] and in one dimension (1D), for which no vortex can exist, solitons and dispersive shock waves (DSW) [22,46,47]. Furthermore, in all dimensions the excess energy can be dissipated into a phonon bath, allowing for a relaxation of the JO.…”
Section: Introductionmentioning
confidence: 99%